2020
DOI: 10.1177/0269215520905041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an integrated transitional care program for stroke survivors living in a rural community: a randomized controlled trial

Abstract: Objective: To evaluate the effect of an integrated transitional care program on health outcomes in stroke survivors based on an original community for healthcare. Design: A pilot randomized controlled trial with blinded assessment. Randomization by statistician using computer-generated, random numbers concealed in opaque envelopes. Setting: A tertiary hospital and participants’ home across Lishui, China. Subjects: A total of 98 people with acute cerebral hemorrhage or cerebral infarction, eight weeks following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 19 publications
0
42
0
4
Order By: Relevance
“…This literature review finally examined 20 articles, of which 19 were RCTs and 1 was an RPT. Regarding international location, 85% of the studies were conducted in Europe [Norway ( 10 15 ): 6, Denmark ( 16 20 ): 5, Netherlands ( 21 ): 1, Sweden ( 22 , 23 ): 2, UK ( 24 , 25 ): 2, Portugal ( 26 ): 1], 10% were conducted in Asia [China ( 27 ): 1, Hong Kong ( 28 ): 1], and 5% were conducted in North America [USA ( 9 ): 1]. For the intervention types, seven studies provided type I intervention, whereas 13 studies provided type II intervention.…”
Section: Resultsmentioning
confidence: 99%
“…This literature review finally examined 20 articles, of which 19 were RCTs and 1 was an RPT. Regarding international location, 85% of the studies were conducted in Europe [Norway ( 10 15 ): 6, Denmark ( 16 20 ): 5, Netherlands ( 21 ): 1, Sweden ( 22 , 23 ): 2, UK ( 24 , 25 ): 2, Portugal ( 26 ): 1], 10% were conducted in Asia [China ( 27 ): 1, Hong Kong ( 28 ): 1], and 5% were conducted in North America [USA ( 9 ): 1]. For the intervention types, seven studies provided type I intervention, whereas 13 studies provided type II intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one randomised controlled trials compared home-based rehabilitation with institution-based rehabilitation on an inpatient or outpatient basis 23–43. Fifteen randomised controlled trials compared home-based rehabilitation with usual care, which was provided according to routine practice without the involvement of the research team and might include no therapy, home care, instructions for home rehabilitation, inpatient therapy and outpatient therapy 32 38 44–56. Five randomised controlled trials evaluated the effect of specific home-based interventions by comparing with blank control or sham control 57–61.…”
Section: Resultsmentioning
confidence: 99%
“…There were various home-based interventions performed in the included studies. Twelve studies did not describe the details of treatment strategy 28 29 32 33 37 43 48 50 52 56 68 70. Among 37 studies which reported the details of treatment strategy, 19 studies provided physical exercise practice,23 26 27 31 34–36 45–47 49 53 57–59 61 63 64 71 20 studies provided training of daily activities,23–27 30 36 38 45 46 53–55 58–61 65 66 71 8 studies provided task/functional-specific training35 39–42 51 61 69 and 2 studies provided constraint-induced movement treatment 44 62.…”
Section: Resultsmentioning
confidence: 99%
“…No que diz respeito às ações em saúde aplicadas durante a internação, embora poucos estudos tenham implementado intervenções terapêuticas no ambiente intra-hospitalar, observou-se concordância entre os autores, acerca do papel de planos de alta especializados, que se constituem como o alicerce de Programas de Transição de Cuidados para idosos (Gilbert et al, 2021;Deng et al, 2020;Murphy et al, 2019;Aboumatar et al, 2018;Ballard et al, 2018;Low et al, 2017;Takahashi et al, 2016;Heim et al, 2016;Zhou et al, 2015;Wong et al, 2015;Naylor et al, 2013;Stauffer et al, 2011). Vale destacar que, para Hanan et al (2018), os planos de alta devem apresentar componentes como: orientações para paciente, familiares e/ou cuidador acerca do prognóstico e terapêutica medicamentosa e de reabilitação que será adotada em domicílio; agendamento de consulta de retorno, com média de até sete dias após alta hospitalar; orientações acerca de possíveis eventos adversos relacionados ao estado de saúde, orientações e encaminhamento para a equipe de Atenção Primária à Saúde sobre o caso.…”
Section: Discussionunclassified